Phylogeny and species delimitation of Strobilomyces (Boletaceae), with an emphasis on the Asian species - Han, L.H. (Persoonia, 2019)
Strobilomyces is broadly distributed geographically and serves an important ecological function. However, it has been difficult to delimit species within the genus, primarily due to developmental variations and phenotypic plasticity. To elucidate phylogenetic relationships among species within the genus and to understand its species diversity, especially in Asia, materials of the genus collected from five continents (Africa, Asia, Australia, Europe, and North/Central America) were investigated. The phylogeny of Strobilomyces was reconstructed based on nucleotide sequences of four genes coding for: the largest and the second largest subunits of the RNA polymerase II (RPB1 and RPB2); the translation elongation factor subunit 1-α (TEF1); and the mitochondrial cytochrome oxidase subunit 3 (COX3). The combined results based on molecular phylogenetics, morphological characters, host tree associations, and geographical distribution patterns support a new classification consisting of two sections, sect. Strobilomyces and sect. Echinati. Using the genealogical concordance phylogenetic species recognition (GCPSR) approach, at least 33 phylogenetic species in Asia can be delimited, all of which are supported by morphological features, and five phylogenetic species remain to be described. The mountainous region of Southwest China is especially special, containing at least 21 species and likely represents a centre of diversification. We further compared our specimens with the type specimens of 25 species of Strobilomyces. Our comparisons suggest that, there are a total of 31 distinct species, while S. sanmingensis, S. verruculosus, S. subnigricans, and S. zangii/S. areolatus, are synonyms of S. mirandus, S. giganteus, S. alpinus and S. seminudus, respectively. Eight new species, namely, S. albidus, S. anthracinus, S. calidus, S. cingulatus, S. densisquamosus, S. douformis, S. microreticulatus and S. pinophilus, are described. A dichotomous key to the Asian Strobilomyces species is provided.